The Literary Impulse and the Ag Communicator - Kathy Kendall (Journal of Applied Communications, 1983)
If Shakespeare and his mythical sister were alive today, chances are they might be ag communicators. When I first thought about that, it seemed far-fetched, even ridiculous, but look at the facts of life for writers.